The impact of axial flow misalignment on a tidal turbine. (December 2017) - Frost, Carwyn H.; Evans, Paul S.; Harrold, Magnus J.; Mason-Jones, Allan; O'Doherty, Tim; O'Doherty, Daphne M.
Abstract: Extensive Research and Development have helped drive the tidal energy industry towards commercial viability, with full-scale prototypes starting to meet marine environmental challenges. This paper utilises velocity data collected from a site off the welsh coast with Computational Fluid Dynamics (CFD) to determine the effects of misaligned flows on the performance of a tidal stream turbine. The field observations indicate that the majority of the currents tend to fall within ±20° of the principal flow direction for economically viable velocities. The CFD modelling suggests a reduction in the non-dimensional performance parameters as the angle of misalignment increases between the axis of rotation and the free stream velocity. The resultant magnitude of the bending moments acting on the rotor end of the driveshaft for the misaligned turbines was found to be up to ten times greater than the aligned turbine. The paper also shows that an accurate definition of the tolerance to axial flow misalignment between the free stream velocity and the axis of rotation of a turbine is required to prevent any negative effects on performance and loading. Highlights: CFD modelling study examining flow misalignment on tidal turbine performance. Velocities tend to fall within a ±20° misalignment to the principle flow direction. Non-dimensional performance parameters reduce as angles of misalignment increase. Using field data for numerical simulations will help increase investor confidence.